ESTOMATOLOGÍA DEPORTIVA. - Cossio Bolaños, Wilberto (1998)
A revision of the literature of the different descriptions of estomatology in relation with the practice ofphysical activities has been done identifijing damiages that may occur during sport compotition, its treatment and prevention. With this work and my experience pretend to offer a prospect to specialists in sport medicine and dentists that can enter an education equipment and assist to sport events and people who practice physical activities.